Synthesis and Characterization of Edible Film Based on Glucomannan from Local Porang Tubers with a Combination of Carrageenan and Sorbitol as Plasticizer - Afriyani, Hapin; Herasari, Dian; Amrulloh, Hanif; Faranida, Qori Hikmah; Ramadani, Arip; Afifah, Nida Rafa; Indriani, Marcella; Theledi, Karim; Aluko, Olukemi (Biota, 2024)
In this study, edible films were made from glucomannan from local porang tubers, carrageenan, and sorbitol as the plasticizer. This research method begins with the making of modified porang flour with three immersion treatments, namely control (A), 10% lime solution (B), and modified lime and mocaf starter fermentation (C) to reduce oxalate levels. Plasticizers were added with variations of carrageenan 2;3;4%, and sorbitol 1;2;3;4; and 5 g. The results showed that the modified lime immersion and fermentation treatment reduced calcium oxalate levels, and the highest yields of glucomannan were 2.58% and 10.07 g. The FTIR analysis results of the isolated glucomannan showed that the spectrum formed by the presence of O-H functional groups, CH2 groups, C-O-C groups, absorption areas of 805 cm-1 and 872 cm-1 indicated the presence of the main constituent of glucomannan, namely β-pyranose. In comparison, the characteristics of the edible film obtained an average thickness between 0.32–1.50 mm. The highest thickness was obtained in the composition of the addition of 3% carrageenan and 4 grams of sorbitol variation C. The percentage of water resistance of edible film variations A and C ranged from 10.04% - 22.02%. Variations A and C with a composition of 2% carrageenan and 1 gram of sorbitol, the edible film is completely degraded. The surface morphology of the edible film obtained from variation A with a concentration of 2% carrageenan and 5 grams of sorbitol showed a slightly porous surface.